Accuracy and reproducibility of fetal‐fraction measurement using relative quantitation at polymorphic loci with microarray. (3rd May 2018) - Schmid, M.; White, K.; Stokowski, R.; Miller, D.; Bogard, P. E.; Valmeekam, V.; Wang, E.
ABSTRACT: Objectives: Various methods of fetal‐fraction measurement have been employed in conjunction with different approaches to cell‐free DNA testing for fetal aneuploidy. In this study, we determined the accuracy and reproducibility of fetal‐fraction measurement using polymorphic assays that are incorporated into the test design as part of the Harmony® prenatal test and evaluated whether the single nucleotide polymorphisms selected for and used in these assays can be applied broadly to all patient populations. Methods: Clinical maternal plasma samples were assayed using a custom microarray with Digital ANalysis of Selected Regions (DANSR) assays designed to cover non‐polymorphic targets on chromosomes of interest for aneuploidy assessment (13, 18, 21, X and Y) and polymorphic targets for fetal‐fraction assessment. In a consecutive series of 47 512 maternal plasma samples, fetal‐fraction measurements based on polymorphic assays were compared with those from Y‐sequence quantitation. Reproducibility was examined between first‐ and second‐tube measurements for the same patient sample in 734 cases. The fraction of informative loci was calculated for 13 988 samples. Results: There was a strong correlation between fetal fractions determined using the polymorphic assays and using Y‐chromosome sequence quantitation ( r = 0.97). Fetal‐fraction measurement between the first and second tubes was highly reproducible ( r = 0.98). The fraction of informative loci observed in a clinical series was consistent with predictions based on assay design. Conclusions: The method based on relative quantitation at polymorphic loci on a microarray is accurate and reproducible for fetal‐fraction estimation and is equally informative across global populations. This study provides a useful benchmark for ensuring the reliability and accuracy of fetal‐fraction measurement. © 2018 Roche Sequencing Solutions. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.